Persepsi Masyarakat Petani Terhadap Manfaat dan Kondisi Lingkungan Danau Batur: Perception of the Farming Community on Benefits and Environmental Conditions of Lake Batur - AKIRA LUSIA; TEGUH PRAYOGO; SITI ZULAIKHA; LESTARIO WIDODO; YUDHI SOETRISNO GARNO (BRIN Publishing (Penerbit BRIN), 2023)
Lake Batur, the largest lake in Bali, has various functions, including raw materials, for clean water, tourism objects, aquaculture, water for agriculture, environmental functions, and transportation. The various functions of the lake by the community in the Lake Batur area are now more utilized as a medium for fish cultivation in floating net cages (KJA), food crops, fruits, and various vegetables. Now they are concerned because the increase in KJA has exceeded its carrying capacity, so the waste it produces causes water quality problems, which threatens the sustainability of the KJA cultivation marked by mass fish deaths that occur every year. It is necessary to conduct a study about this phenomenon to determine the aspirations or opinions and understanding of environmental conditions in sustaining farming activities. Aspirations have been obtained by interviewing the Lake Batur farming community. The study results show that the community believes that the current environmental conditions of Lake Batur are still good and can provide decent and profitable results for both KJA fisheries and agricultural businesses. In principle, the community is aware of the economic dependence of its life on the existence of Lake Batur. The community does not want the balance of Lake Batur to be disturbed and if it is disturbed, the community is willing to cooperate with the government to restore it in any way, including monetary contributions. ABSTRAK Danau Batur, danau terbesar di Bali, memiliki bermacam-macam fungsi, antara lain bahan baku air bersih, obyek wisata, budidaya perikanan, air untuk pertanian, fungsi lingkungan, dan transportasi. Berbagai fungsi danau tersebut oleh masyarakat di kawasan Danau Batur kini lebih dimanfaatkan sebagai media budidaya ikan di keramba jaring apung (KJA), tanaman pangan, buah-buahan, dan aneka sayuran. Saat ini masyarakat kawatir, karena peningkatan KJA telah melampaui daya dukungnya sehingga limbah yang dihasilkannya menyebabkan masalah kualitas air, yang justru mengancam keberlanjutan budidaya dengan KJA tersebut yang ditandai dengan kematian masal ikan yang terjadi setiap tahun. Berkenaan dengan fenomena tersebut maka dirasakan perlu dilakukan kajian untuk mengetahui aspirasi atau pendapat dan pemahaman terhadap kondisi lingkungan dalam menopang kegiatan usaha tani. Aspirasi telah diperoleh dengan cara wawancara kepada masyarakat petani Danau Batur. Hasil kajian menunjukkan bahwa masyarakat berpendapat kondisi lingkungan Danau Batur saat ini masih baik dan dapat memberikan hasil layak dan menguntungkan baik untuk usaha perikanan KJA maupun usaha pertanian. Pada prinsipnya masyarakat sadar akan ketergantungan ekonomi kehidupannya terhadap keberadaan Danau Batur. Masyarakat tidak ingin keseimbangan Danau Batur terganggu dan jika terganggu, masyarakat bersedia bekerja sama dengan pemerintah untuk memulihkannya dengan cara apapun, termasuk kontribusi uang.